2022
DOI: 10.3389/fphar.2022.970597
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical characteristics of mesalazine-induced cardiotoxicity

Abstract: Background: Mesalazine is the first-line inflammatory bowel disease (IBD) treatment. However, it can cause fatal cardiotoxicity. We aimed to analyze the clinical characteristics of mesalazine-induced cardiotoxicity and provide evidence for clinical diagnosis, treatment, and prevention.Methods: We collected Chinese and English literature on mesalazine-induced cardiotoxicity from 1970 to 2021 for retrospective analysis.Results: A total of 52 patients (40 males and 12 females) were included, with a median age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…LVEDD and LVESD were increased in the Ber-pretreated group compared with the DOX group ( Figure 1 A,B). Usually, cardiac injury is accompanied by the release of enzymes such as creatine kinase (CK) into the blood [ 36 ]. In our study, as shown in Figure 1 C, DOX increased serum CK levels from 1378.8 ± 225.1 U to 2640 ± 443.8 U. Pretreatment with Ber markedly reduced the elevated CK content to 1586.5 ± 170.8 U.…”
Section: Resultsmentioning
confidence: 99%
“…LVEDD and LVESD were increased in the Ber-pretreated group compared with the DOX group ( Figure 1 A,B). Usually, cardiac injury is accompanied by the release of enzymes such as creatine kinase (CK) into the blood [ 36 ]. In our study, as shown in Figure 1 C, DOX increased serum CK levels from 1378.8 ± 225.1 U to 2640 ± 443.8 U. Pretreatment with Ber markedly reduced the elevated CK content to 1586.5 ± 170.8 U.…”
Section: Resultsmentioning
confidence: 99%
“…Mesalazine has been shown to inhibit the activity of COX1 and enhance the metabolism of arachidonic acid into lipoxygenase products such as leukotrienes. The excessive production of lipoxygenase products can contribute to a pro-inflammatory signaling cascade, thereby promoting the development of allergic myocarditis [ 12 ]. This process involves the release of cytokines that stimulate eosinophils, leading to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mesalazine has been found to induce the formation of reactive oxygen species, which disrupt mitochondrial membrane. This causes mitochondrial dysfunction and subsequent release of cytochrome c, eventually leading to cardiomyocyte apoptosis and eventually to cardiovascular dysfunction [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation